Analysis of the Reconfiguration of Indonesia’s Air Defense Strategy Based on Geospatial Intelligence Amid the Geopolitical Dynamics of theIndo-Pacific - Wahyu Prabowo; Ella Syafputri Prihatini; Usni Hasnudin (Al-Makki Publisher, 2026)
This study examines how Indonesia’s air defense strategy should be reconfigured around Geospatial Intelligence (GEOINT) to address the evolving dynamics of Indo-Pacific geopolitics following the 2026 United States–Israel war against Iran, a conflict that exposed the vulnerability of air defense systems to mass missile and drone attacks despite technological superiority. Using a qualitative descriptive-analytical approach involving in-depth interviews, documentation analysis, and observation, the data were analyzed using Miles, Huberman, and Saldaña’s interactive model and validated through source and methodological triangulation. The study draws on informants from the Air Force, Army, and academia, as well as internal Indonesian National Armed Forces (Tentara Nasional Indonesia [TNI]) documents. The findings demonstrate that the conflict fundamentally shifted the nature of aerial threats from manned aircraft toward missile systems and drone swarms, revealing Indonesia’s reliance on a platform-centric doctrine that is insufficient for addressing cognitive-overload and cost-imposition warfare. The gap between Indonesia’s current GEOINT capabilities and the ideal requirements of a layered air defense system is multidimensional, encompassing technological capacity, human resources, command-and-control integration, and the challenges posed by the country’s archipelagic geography. This study proposes a five-pillar reconfiguration model that positions GEOINT as the core integrator, develops a network-centric warfare architecture, acquires strategic force-enabling assets, strengthens GEOINT analyst capabilities, and transforms institutional structures toward a hub-and-spoke model. The implementation is sequenced across three strategic time horizons using the Eisenhower Matrix. The study recommends amending the Swa Bhuwana Paksa doctrine to institutionalize GEOINT as the foundation of Indonesia’s layered air defense strategy.